Analisis Strategi Komunikasi Pemasaran Digital Amura Beauty Care melalui Konten Storytelling Berdasarkan Teori AIDDA - Vania Juliana; Amiruddin Saleh (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The development of social media in digital marketing communication has encouraged skincare brands to utilize storytelling content as a persuasive communication strategy. However, studies on the application of the AIDDA theory in storytelling content on the TikTok platform are still limited. This study aims to analyze the digital marketing communication strategy through storytelling content on the TikTok account @amurabeautycare based on the AIDDA theory (Attention, Interest, Desire, Decision, Action). This research used a descriptive qualitative method with purposive sampling techniques and data collection through observation, interviews, and documentation of 4 storytelling contents during the January–April 2026 period. The results show that storytelling content consistently applies the AIDDA stages and forms a communication strategy based on audience experience with a problem–solution–result pattern. This strategy is strengthened through a soft selling approach and emotional triggers. In conclusion, storytelling content is effective in building emotional closeness, trust, and encouraging audience action